Investigating solar harvesting in various greenhouse designs with semi-transparent PV panels on roofs and sidewalls - Mohammadreza Gholami (17032317) (2025)
The growing demand for clean and sustainable agricultural practices underscores the potential of integrating renewable energy technologies into greenhouse (GH) systems as an effective solution. In regions like Doha, Qatar, where high solar irradiance is abundant, the use of semi-transparent photovoltaic (STPV) technology in GH applications is particularly promising. STPV technology is gaining increasing attention in GH applications due to its dual functionality of generating electricity while allowing sufficient light transmission for plant growth. Despite its potential, limited research has comprehensively examined the power output of STPV systems installed on both the walls and roofs of GHs, particularly across different standard GH designs. This paper addresses that gap by analyzing the total STPV power output for four common GH designs (Even and Uneven Span, Vinery design, and Modified Arch) located in Doha, Qatar case study, each with unique structural characteristics, such as differing roof slopes, wall angles, and surface areas. These variations influence solar irradiance distribution and consequently impact power generation efficiency. Employing a detailed mathematical model that incorporates direct, diffuse, and reflected irradiance, we compare monthly, seasonal, and yearly power outputs for panels positioned on walls and roofs. The findings reveal significant variations in output between the different designs and orientations. Among the designs, the Uneven Span GH achieved the highest total yearly STPV output (6,491 kWh/90.85 kWh/m2), followed by the Modified Arch and Even Span, while the Vinery design produced the least output (4398.86 kWh/73.31 kWh/m2). Moreover, the findings underscore the importance of wall-mounted STPV systems, which often surpass roof-mounted ones in total energy output (up to 57.1 % of the total energy). The sensitivity analysis shows that STPV efficiency is the most influential parameters affecting annual output, while ground reflectivity and roof tilt have a smaller impact. The study emphasizes that, for regions like Doha, Qatar, maximizing STPV power output involves expanding south-facing areas and harnessing the potential of wall-mounted panels. Other Information Published in: Energy and Buildings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.enbuild.2025.116436